Oxidative Stress and Phospholipid Alterations in Destructive Cholecystitis and Cholelithiasis: A Comprehensive Analysis (Asian Journal of Pharmaceutics (AJP), 2025)
Oxidative stress, lipid peroxidation (LPO), and antioxidant depletion are crucial in the pathogenesisof destructive cholecystitis and cholelithiasis. Objectives: This study investigated the influence of these factorson the phospholipid (PL) composition of erythrocyte membranes in patients with acute calculous cholecystitis(ACC), chronic calculous cholecystitis, and gangrenous ACC. Methods: Markers of LPO, antioxidant defense,and endogenous intoxication were measured in blood plasma and erythrocyte membranes. The PL fractions in theerythrocyte membranes were analyzed using thin-layer chromatography. Results: The results showed increasedlevels of diene conjugates and malondialdehyde, indicating significant LPO in destructive cholecystitis cases.Antioxidant defenses were depleted, as evidenced by the decreased total antioxidant activity and catalase levels.Elevated levels of medium-molecular-weight peptides and phospholipase activity indicate systemic inflammatoryresponses and internal intoxication. Notable changes in the erythrocyte membrane PL composition includedincreased lysophosphatidylcholine and reduced phosphatidylcholine levels, suggesting membrane degradation.The increased ratio of easily oxidizable PL fractions to less oxidizable fractions indicates membrane instabilityand oxidative stress. Conclusion: These findings confirm that oxidative stress, PL changes, and weakenedantioxidant defense contribute to the progression of destructive cholecystitis and cholelithiasis. Understandingthese molecular alterations can help identify novel diagnostic markers and therapeutic targets for biliary tractdiseases.